2009
DOI: 10.1021/am900051g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Zirconium Tungstate Filler on the Cure Behavior of a Cyanate Ester Resin

Abstract: In this work, the effect of a negative thermal expansion zirconium tungstate (ZrW2O8) filler on the cure behavior of a unique low-viscosity bisphenol E cyanate ester (BECy) is characterized by differential scanning calorimetry. The cure rate of BECy is found to increase upon the incorporation of ZrW2O8 particles, and the catalytic effect increases with increasing filler loading. The catalytic effect is primarily attributed to the presence and nature of hydroxyl groups on the ZrW2O8 particle surface. In compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…The onset and peak temperatures shift to higher temperatures with increasing heating rate, as expected. The values of T o and T p for neat BECy are found to be systematically higher than the values obtained at the same rate in previous work, 30 which used a different batch of BECy supplied by the manufacturer. Incorporation of pristine CNTs results in a 12-14 C decrease in the onset temperature while incorporation of COOH CNTs decreases the onset temperature by 14-18 C. On the other hand, upon incorporation of OH CNTs the values of T o exhibit a dramatic decrease and are found to be 40-55 C lower than the values of T o for BECy, depending on the rate.…”
Section: Resultscontrasting
confidence: 82%
“…The onset and peak temperatures shift to higher temperatures with increasing heating rate, as expected. The values of T o and T p for neat BECy are found to be systematically higher than the values obtained at the same rate in previous work, 30 which used a different batch of BECy supplied by the manufacturer. Incorporation of pristine CNTs results in a 12-14 C decrease in the onset temperature while incorporation of COOH CNTs decreases the onset temperature by 14-18 C. On the other hand, upon incorporation of OH CNTs the values of T o exhibit a dramatic decrease and are found to be 40-55 C lower than the values of T o for BECy, depending on the rate.…”
Section: Resultscontrasting
confidence: 82%
“…The x-ray diffraction (XRD) spectra for the two powders were also found to be similar apart from slight changes in intensities. 23 It is noted that Perottoni and coworkers 6 suggested that although g-phase can be induced at 200 MPa, differences in XRD and Raman spectra between g-and a-phase ZrW 2 O 8 can only be observed if the g-phase had been induced at pressures of at least 1 GPa. Hence, a possible reason for similarities in the spectra could be that the g-phase had been induced at pressures less than 1 GPa in the as-received powder as a consequence of ball milling and size reduction operations.…”
Section: Resultsmentioning
confidence: 99%
“…19 Preliminary results in our laboratory indicate that substituting the OH with silane groups might mitigate the reduction in T g observed in these composites. 23 The values of CTE at temperatures above and below the glass transition temperature are compared as a function of ZrW 2 O 8 loading in Fig. 11.…”
Section: Resultsmentioning
confidence: 99%
“…The approaches include addition of high-thermoplastic tougheners [12][13][14], rubber inclusions [15][16][17][18], inorganic or organic fillers [19][20][21][22][23], thermosetting resins [24,25], and flexible molecules [26][27][28]. However, these methods are largely ineffective in restoring strength to cracked or damaged material.…”
Section: Introductionmentioning
confidence: 99%